ANALISIS PEMANFAATAN ALOKASI DANA PENDIDIKAN PADA APBD KABUPATEN KUANTAN SINGINGI UNTUK PENINGKATAN MUTU PENDIDIKAN MANUSIA SEKTOR PENDIDIKAN TAHUN 2011-2020 - Ridho Dwianto; Syapsan Syapsan; Hendro Ekwarso (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The purpose of this study is to analyze the impact of allocating the education expenditure budget in the Kuantan Singingi District Budget on improving the quality of human development in the education sector, to find out what factors cause the low growth of the quality of human development in the Education sector in Kuantan Singingi Regency. Data collection techniques: documentation. The Data Analysis method uses multiple linear regression analysis. The results showed that simultaneously education expenditure consisting of employee expenditure, goods and services expenditure and capital expenditure had a significant effect on the quality of human development in the education sector. Partially only spending on goods and services has a significant effect on the quality of human development in the education sector. Factors that cause the low growth of the quality of human development in the education sector are due to the disproportionate distribution of the education expenditure budget, the small expenditure on goods and services while what has a significant effect on the growth of the quality of human development in the education sector is precisely only spending on goods and services. Efforts made to improve the quality of human development in the education sector in Kuantan Singingi Regency include increasing the education expenditure budget in the regional budget every year, allocating proportional education spending and further increasing the expenditure on goods and services because it affects improving the quality of human development in the education sector.